Saberes e fazeres dos professores da área de linguagem, códigos e suas tecnologias, em uma escola do quilombo Itambé/MT - Santos, Silvana Alves dos (2018)
The present study is the result of a qualitative research with ethnographic clipping, carried out at the Quilombola State School Reunidas de Cachoeira Rica, located in the Itambé/Chapada dos Guimarães-MT quilombo. The objective of this research was to analyze and present the knowledge that teachers of the language area mobilize in their pedagogical practices, in the context of the mode of quilombola school education. It also had as purpose to describe the community scenario and the Quilombola State School Reunidas de Cachoeira Rica, in its historical, political, identity and cultural aspects, and to point out how the epistemological field and the public policies are being thought and articulated, focusing on the formation teachers for Quilombola School Education. The basic theoretical foundation is anchored in Almeida (1996), Arroyo (2007, 2013), Barth (1998), Borges (2001), Castilho (2011), Freire (1987, 1992, 2001), Gauthier (1998), Nunes (1999, 2001), Tardif (2014), Sacristán (2000) and Schulman (2005), Leite (2000), Moreira, Silva (1994) Mclaren (2000). The instruments used for the data collection were: participant observation, semi-structured interview, life history, field diary record, documents and photographs. The results point out that the knowledge of the researched teachers come from different sources, but the experiential knowledge stands out as the structuring axes of the pedagogical action and as elements that work alongside other knowledge, enriching the work of the teachers, and it is convenient to stress that even in the face of all the adversities they encounter in the school environment, such as lack of adequate material, lack of didactic and pedagogical resources, they mobilize such knowledge to invest in the preparation of classes and in the didactic transposition of contents. However, it is imperative to point out that the precarious conditions, modest and insufficient in physical and structural terms, currently constitute the major bottleneck for better quality work, as well as more meaningful activities aligned with the quilombola school context and students' experiences. Another component worthy of attention, present in the results, points to the need and the need for continuing education, since the themes pertinent to the quilombola educational modality, offered by the school, do not constitute as the guiding axis of the teaching work, contrary to what is regulated in the official documents that guide the pedagogical doing in quilombola schools or inserted in quilombola territory.